2019
DOI: 10.1093/rb/rbz010
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of in-stent restenosis after graphene oxide double-layer drug coating with good biocompatibility

Abstract: In this study, we designed a double layer-coated vascular stent of 316L stainless steel using an ultrasonic spray system to achieve both antiproliferation and antithrombosis. The coating included an inner layer of graphene oxide (GO) loaded with docetaxel (DTX) and an outer layer of carboxymethyl chitosan (CMC) loaded with heparin (Hep). The coated surface was uniform without aggregation and shedding phenomena before and after stent expanded. The coating treatment was able to inhibit the adhesion and activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…Importantly, the prepared materials do not break down erythrocytes. Hemolysis tests confirmed the results obtained by S. Ge et al [ 17 ]. The coatings with an inner layer of GO loaded with docetaxel and an outer layer of carboxymethyl loaded with heparin, tested by that research group, did not cause hemolysis higher than 5%, which is following the guidelines.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Importantly, the prepared materials do not break down erythrocytes. Hemolysis tests confirmed the results obtained by S. Ge et al [ 17 ]. The coatings with an inner layer of GO loaded with docetaxel and an outer layer of carboxymethyl loaded with heparin, tested by that research group, did not cause hemolysis higher than 5%, which is following the guidelines.…”
Section: Discussionsupporting
confidence: 90%
“…GO can also be used to modify other surfaces, e.g., polymer surfaces, in the production of scaffolds [ 14 , 15 ]. Other studies show that graphene oxide as an intermediate layer in coatings, in combination with heparin and poly(3,4-ethylenedioxythiophene) [ 16 ] or drugs, i.e., docetaxel [ 17 ], may improve the biocompatibility of steel stents and reduce platelet adhesion. Still, the status of graphene oxide as a biomaterial remains unsettled.…”
Section: Introductionmentioning
confidence: 99%
“…This reduction in platelet surface coverage was far greater than the amount of reduction observed for recent heparin drug-eluting stents [ 23 , 24 , 26 ], which showed far more platelet adhesion to their modified steel samples as compared to MEG-OH-coated samples, and poorer reduction in adhesion of less than 80% compared to the greater-than-90% adhesion observed for MEG-OH. Additionally, the amount of platelet reduction was greater than that observed for recent graphene surface coatings on steel which display an 80–90% reduction [ 30 , 31 , 32 ], and performed similarly to hydrogel coatings, with a greater-than-90% reduction [ 33 , 34 ]. As such, MEG-OH performs as well or better than the so-called state-of-the-art alternative coatings as it pertains to the prevention of thrombus formation.…”
Section: Resultsmentioning
confidence: 96%
“…Graphene-coated stents have also been investigated for their anti-thrombogenic properties on stainless steel [ 30 , 31 , 32 ]. These coatings may show greater reduction in platelet adhesion compared to heparin-eluting stents, with some reducing adhesion by 80–90%, but these also show slightly elevated cytotoxicity compared to bare stents.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxide (GO), a highly oxidized form of graphene, in which the quasi-two-dimensional (2D) spatial structure of carbon atoms is decorated with oxygen-containing functionalities [ 11 ]. Numerous oxygen-functional groups, including carboxylic, epoxy and hydroxyl groups make its surface open for covalent, electrostatic and hydrogen bonding with biomolecules and therapeutic drug, which endows drugs with targeted and sustained features, and improves the biocompatibility of GO [ 12 ]. Studies have reported that GO has the potential to promote cellular proliferation, differentiation and adhesion with no or little cytotoxic effect [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%